The Influence Of Motivation And Compensation On The Performance Of Nongsa Sub-District Employees In Batam City With Loyalty As An Intervening Variable - Dedi Sureno; Suhardi, Suhardi (Jurnal Ekonomi, 2024)
This study aims to analyze the effect of motivation and compensation on employee performance in Nongsa Subdistrict, Batam City with loyalty as an intervening variable. and also examine the effect of loyalty on employee performance, as well as the role of loyalty as an intervening variable in the relationship between motivation and performance, as well as between compensation and employee performance. The research method used is quantitative with the number of respondents as many as 111 employees in the Nongsa District. Data analysis was carried out using SEM PLS SmartPLS 4 software. The results of the analysis show that compensation has a significant effect on employee performance and loyalty. Loyalty also has a significant effect on employee performance. Motivation has a significant effect on employee performance and loyalty. In addition, loyalty mediates the effect of motivation on employee performance and the effect of compensation on employee performance. All relationships studied show a significant effect, indicating that both compensation and motivation play an important role in improving employee performance through increased loyalty. The results of this study are expected to provide a comprehensive insight into how motivation and compensation can influence employee performance and loyalty, as well as the importance of loyalty as a mediating factor in these relationships.